2014
DOI: 10.1136/bjophthalmol-2014-304943
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated versus standard corneal collagen crosslinking combined with same day phototherapeutic keratectomy and single intrastromal ring segment implantation for keratoconus

Abstract: A combined treatment of accelerated CXL preceded by same day t-PTK and single ICRS is as effective as the combined treatment using standard CXL for visual rehabilitation in progressive keratoconus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 23 publications
1
41
0
Order By: Relevance
“…This is consistent with the findings reported in other series evaluating the results of transepithelial CXL, either by iontophoresis or accelerated. [19][20][21][22][23][24][25][26][27] Similarly, in line with all previous studies on transepithelial CXL, 19-27 a significant improvement in CDVA was observed after surgery that remained throughout the entire 12-month follow-up period. Lesniak and Hersh,24 in a prospective study, evaluated a similar technique and found a mean improvement in CDVA of 0.83 Snellen lines.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…This is consistent with the findings reported in other series evaluating the results of transepithelial CXL, either by iontophoresis or accelerated. [19][20][21][22][23][24][25][26][27] Similarly, in line with all previous studies on transepithelial CXL, 19-27 a significant improvement in CDVA was observed after surgery that remained throughout the entire 12-month follow-up period. Lesniak and Hersh,24 in a prospective study, evaluated a similar technique and found a mean improvement in CDVA of 0.83 Snellen lines.…”
Section: Discussionsupporting
confidence: 77%
“…Other studies have evaluated changes in the maximum keratometry after different modalities of transepithelial CXL. [19][20][21][22][23][24][25][26][27] Lesniak and Hersh 24 found a mean reduction of 0.9D in the maximum keratometry in a prospective study that evaluated the results of a similar CXL technique than that used in our study over a 6-month period. It should be borne in mind that this study included keratoconus cases that were more advanced than in our series, so the mean keratometry was higher.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, several studies have evaluated with very good results the combination of cross-linking treatments and implants of intrastromal rings, because it is postulated that the first is the only effective treatment to stop the progression of the disease and the second for visual and refractive improvement without having a great implication in its progression [17][18][19][20][21]. ICRs combined with CXL showed that UDVA improved 0.12 logMAR at 12 months of follow-up, CDVA worsened 0.03 logMAR at 12 months of follow-up, but the mean sphere and cylinder component improved 3.03 ± 1.99 and 1.99 ± 0.96 D, respectively, at 12 months of follow-up.…”
Section: Intrastromal Corneal Ringsmentioning
confidence: 99%
“…8 The next step is vision correction. In case of lens opacification we perform phacoemulsification with toric customized intraocular lens (IOL) implantation (AT Torbi 709M), or (if a lens is clear) we implant posterior phakic IOL.…”
Section: Stages Of Keratoconus Treatmentmentioning
confidence: 99%